Australian Journal of Advanced Nursing March - May 2015 Vol.32 No.3 - Redaksi (Australian Nursing Federation, 2015)
- Public health nurses experiences of their role as part of a primary care team - Patient satizfaction with their pain management and comport level after open heart surgery - Radiation awareness among nurses in nuclear medicine - A nurses guide to qualitative research - Development of a nurse practitioner led carpal tunnel syndrome clinic